ANALISIS PENDISTRIBUSIAN REVENUE SHARING DALAM AKUNTANSI SYARIAH UNTUK MENCAPAI PRINSIP KEADILAN BERDASARKANFATWA DSN NO: 15/DSN-MUI/IX/2000 (Studi Kasus PT Bank Aceh Syariah) - Indrayani Indrayani; Sri Indriyani; Razif Razif (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This study aims to determine whether the distribusion of profit sharing in Islamic accounting using revenue sharing is fair based on the fatwa DSN NO:15/DSN-MUI/IX/2000. This study uses a descriptive qualitative research method where the researcher canducts research to determine the value of the independent variable, either one or more variables without making comparisons or linking one variable to another. The results show that the distribusion of revenue sharing that applies sharia accounting has distributed the profit sharing to fund owners, employees, government, zakat and reserves according to Islamic values based on the fatwa DSN NO:15/DSN-MUI/IX/2000. Meanwhile, from a fairness point of view, it has not been fully implemented because the profit sharing received by shareholders is reater than that of customers.